The Influence of Destination Image, Tourists Satisfaction, and Tourists Experience toward Revisit Intention to The Most Beautiful Village in The World (Nagari Tuo Pariangan) - Weldera Purnama; Yunia Wardi (Jurnal Kajian Manajemen dan Wirausaha, 2019)
Purpose - The purpose of this research are to analyze : (1) The effect of the destination image on the revisit of tourist intention coming to visit the Most Beautiful Village in the World (Nagari Tuo Pariangan), (2) The effect of tourists satisfaction on the revisit intention of tourists who come to visit the Most Beautiful Village in the World (Nagari Tuo Pariangan), (3) The effect of tourist experience on the revisit intention of tourists who come to visit the Most Beautiful Village in the World (Nagari Tuo Pariangan)Methodology - The type of this research is Causative research. The population on this research were foreign, domestic and local tourists who had visited Nagari Tuo Pariangan, Tanah Datar Regency, West Sumatra with the total sample is 151 persons which was taken by using purposive sampling due to unknown the number of population.Finding - Regarding the causal model proposed, the data confirm the relationship set out in the hypothesis. It can therefore be stated that (1) Destination image has a positive effect and significant to revisit intention (2) Tourists satisfaction has a positive effect and significant to revisit intention (3) Tourists experience has a positive effect and significant to revisit intention.Conclusion - The analysis highlights the positive influence which taking part in the destination image, tourists satisfaction, and tourists experience toward revisit intention. This is the clearly shows in this relationship from the empirical point-of-view.Limitation - This research only limit with some variables Keywords: Destination Image, Tourists Satisfaction, Tourists Experience, Revisit Intention